2019
DOI: 10.1007/jhep08(2019)068
|View full text |Cite
|
Sign up to set email alerts
|

Black hole chemistry and holography in generalized quasi-topological gravity

Abstract: We investigate the thermodynamics of AdS black holes in Generalized Quasitopological Gravity with and without electric charge, concentrating on the version of the theory that is cubic in curvature. We study new aspects of Hawking-Page transitions that occur for these black holes. Working within the framework of black hole chemistry, we find a variety of familiar and new critical behaviour and phase transitions in four and higher dimensions for the charged black holes. We also consider some holographic aspects … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 114 publications
(160 reference statements)
6
43
0
Order By: Relevance
“…Since including quartic quasi-topological or Lovelock terms into the action does not alter the black hole entropy from its Einstein gravity value [34], only quartic GQG contributions are responsible for the occurrence of this pole. A previous study of cubic GQG found that similar behaviour for η/s took place [84].…”
Section: Holographic Hydrodynamicssupporting
confidence: 60%
See 4 more Smart Citations
“…Since including quartic quasi-topological or Lovelock terms into the action does not alter the black hole entropy from its Einstein gravity value [34], only quartic GQG contributions are responsible for the occurrence of this pole. A previous study of cubic GQG found that similar behaviour for η/s took place [84].…”
Section: Holographic Hydrodynamicssupporting
confidence: 60%
“…In studying the behaviour at this point, we note that the equations of state need to be solved for these specific parameter values, instead of using (4.13) and (4.14), since the latter becomes invalid if the denominator of t c vanishes. If both couplings are non-zero, again the denominator of T c in (4.11) is quartic in v 2 , and a similar procedure can be employed to write a formula for α 4 in terms of β 3 and e. Doing so, we find that for any values of the parameters the only solution is α 4 = 0, however in cubic gravity critical temperature does not have a singularity in four dimensions [84]. In other words, this particular occurrence of this apparent thermodynamic singularity is obtained only in Einstein-quartic GQG (for which the cubic coupling vanishes).…”
Section: Critical Behaviour In Four Dimensionsmentioning
confidence: 94%
See 3 more Smart Citations